Social Media and Academic Performance of the Student in Nepal - Rabi Kumar Bhattarai (Journal of Business and Social Sciences, 2025)
This study analyzes the impact of social media on students’ day to day lives and learning environment in Makawanpur, Nepal. The study highlighted students' social media usage levels and how they affect their behaviour, academic outcome, and mental health. The study used a mixed-methods research design. 150 students were used as respondence for data collection, in rural and urban settings, using tools like surveys, interviews, and field observations. The results showed that while social media contributes to academic achievement through helping assess the educational content, excessive and uncontrolled use causes distraction, emotional stress, and exposure to cyberbullying. The findings from the study aim to support future planning and policy formulation, and also create an awareness program for students’ well-being.